Association between composite dietary antioxidant index and handgrip strength in American adults: Data from National Health and Nutrition Examination Survey (NHANES, 2011-2014) - Wu, Dongzhe; Wang, Hao; Wang, Wendi; Qing, Chang; Zhang, Weiqiang; Gao, Xiaolin; Shi, Yongjin; Li, Yanbin; Zheng, Zicheng (Frontiers in Nutrition, 2023)
Purpose: The association between CDAI and HGS is currently unclear. This study investigated the association between CDAI(including its components) and HGS in 6019 American adults. Method: The research data were selected from the 2011-2014 National Health and Nutrition Survey(NHANES), and a total of 6019 American adults were screened and included. A weighted generalized linear regression model was used to evaluate CDAI(including its components) and HGS.(4)Results:(1) CDAI was significantly positively correlated with HGS (β =0.009, 0.005~0.013, P<0.001), and the trend test showed that compared with the lowest quartile of CDAI, the highest quartile of CDAI was positively correlated with HGS (β=0.084, 0.042~0.126, P =0.002). Gender subgroup analysis showed that male CDAI was significantly positively correlated with HGS (β =0.015, 0.007~0.023, P= 0.002), and compared with the lowest quartile of CDAI, the highest quartile of CDAI was positively correlated with HGS (β=0.131, 0.049~0.213, P=0.006) and the trend test was significant (P for trend<0.0100). (2)The intake of dietary vitamin E, Zinc, and Selenium showed a significant positive correlation with HGS (β= 0.004, 0.002~0.007, P= 0.006; β=0.007, 0.004~0.009, P< 0.001; β=0.001, 0.001~0.001, P<0.001), vitamin A, vitamin C and carotenoid were significantly associated with HGS in the Crude Model, but this significant association disappeared in the complete model with the increase of control variables. Gender subgroup analysis showed that in model 3, male dietary intake levels of vitamin E, Zinc, and Selenium were significantly positively correlated with HGS (β=0.005, 0.002~0.009, P=0.011; β=0.007, 0.004~0.011, P=0.001; β=0.001, 0.001~0.001, P=0.004), the rest of the indicators had no significant correlation with HGS. Among the female subjects, dietary zinc intake was significantly positively correlated with HGS (β=0.005, 0.001~0.008, P=0.008), and there was no significant correlation between other indicators and HGS (P>0.05). (5)Conclusion: There was an association between the CDAI and HGS, but there was a gender difference, and there was an association between the CDAI and HGS in male, but the association was not significant in female. Intake of the dietary antioxidants vitamin E, selenium, and zinc was associated with HGS in male, but only zinc was associated with HGS among dietary antioxidants in female.